2014
DOI: 10.5539/ijef.v6n9p117
|View full text |Cite
|
Sign up to set email alerts
|

Foreign Direct Investment and Economic Growth: Evidence from Bangladesh

Abstract: This paper examines the relationship between foreign direct investments and economic growth of Bangladesh during the period 1972-2011. After reviewing the literature on the factors affecting the growth of the economy of the country, the paper empirically evaluates the most significant factors that may influence the growth of the economy of Bangladesh during the period of 1972-2011. This study evaluates the association between FDI and economic growth using multiple regression method by considering relationship … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 50 publications
2
12
0
1
Order By: Relevance
“…The previous literature on FDI and economic growth nexus in Bangladesh, for example, Shimul et al (2009), using a smaller dataset , utilized the ARDL technique, and found no causal relationship between FDI and economic growth. Conversely, Tabassum and Ahmed (2014), using data for the period 1972-2011 and applying a multiple regression model, found FDI to be insignificant in influencing economic growth. Therefore, the literature is limited on the selected topic in the case of Bangladesh.…”
Section: Introductionmentioning
confidence: 98%
“…The previous literature on FDI and economic growth nexus in Bangladesh, for example, Shimul et al (2009), using a smaller dataset , utilized the ARDL technique, and found no causal relationship between FDI and economic growth. Conversely, Tabassum and Ahmed (2014), using data for the period 1972-2011 and applying a multiple regression model, found FDI to be insignificant in influencing economic growth. Therefore, the literature is limited on the selected topic in the case of Bangladesh.…”
Section: Introductionmentioning
confidence: 98%
“…Conversely, GC results suggest that there is no causality relationship between GDP and FDI for Bangladesh and a unidirectional relationship was found for Pakistan and India, which means FDI caused economic output in Pakistan. Tabassum and Ahmed (2014) [14] examined the relationship between foreign direct investments and economic growth of Bangladesh during the period 1972-2011. The results indicate that domestic investments exert a positive influence on economic growth whereas foreign direct investments and openness of trade are less significant.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This was contradicting with the result obtained by Ousseini, Hu and Aboubacar (2015) in which there was no significant relationship between FDI and economic growth in Nigeria compared to domestic investment. Tabassum and Ahmed (2014) highlighted that FDI was less significant on Bangladesh's economic growth compared to domestic investment. However in 2016, Hussain and and Haque proved that by adopting The Vector Error Correction Model (VECM) on annual data from 1973 to 2014, FDI became an impact factor on Bangladesh's economic growth.…”
Section: Literature Reviewmentioning
confidence: 99%
“…such as better growth potential, cheaper workforce and highly-skilled labor to Besides that, FDI encourages job opportunities, increases output, generates competition among local business and achieves advantages through technological knowledge enhancement and innovative capability of other firms and countries (Denisia, 2010). Tabassum and Ahmed (2014) state that FDI generates higher exports, replacement of bank loan, association to foreign markets and currencies especially among developing countries. FDI can be done either by establishing new businesses, joint venture with foreign businesses or by acquiring foreign asset in the host county.…”
Section: Introductionmentioning
confidence: 99%